The environmental culture of the teachers of Earth and environment sciences in the schools of northern Jordan Valley Brigade and the extent of their practice in light of some variables - Wala Taleb; Amal Malkawi (Deanship of Scientific Research (DSR), the University of Jordan, 2020)
This study aimed to investigate the level of environmental culture among Earth and environment sciences teachers in the northern Jordan valley brigade schools in light of some variables, and the positive practices towards the environment. The study sample consisted of (86) teachers, (55) female teachers and (31) male teachers, who taught Earth and environment sciences. Questionnaires were designed and were applied to the study sample to measure the positive practices towards the environment. The study results showed that the level of environmental knowledge among teachers was of moderate level with a score of (76%). The level of environmental practice among earth and environmental science teachers was moderate with a score of (63%), and there were no statistically significant differences in the level of environmental knowledge among teachers and their practice according to variables of gender, scientific qualification, and experience. The results indicated that there was a positive and strong relationship between the level of environmental knowledge of teachers and the level of environmental practice. The study recommended that earth and environment sciences teachers from different schools should be encouraged to exchange ideas, information and experiences related to environmental culture.